Diversity and Distribution of Archaea Community along a Stratigraphic Permafrost Profile from Qinghai-Tibetan Plateau, China - Wei, Shiping; Cui, Hongpeng; He, Hao; Hu, Fei; Su, Xin; Zhu, Youhai (Archaea, 2014)
Accompanying the thawing permafrost expected to result from the climate change, microbial decomposition of the massive amounts of frozen organic carbon stored in permafrost is a potential emission source of greenhouse gases, possibly leading to positive feedbacks to the greenhouse effect. In this study, the community composition of archaea in stratigraphic soils from an alpine permafrost of Qinghai-Tibetan Plateau was investigated. Phylogenic analysis of 16S rRNA sequences revealed that the community was predominantly constituted by Crenarchaeota and Euryarchaeota . The active layer contained a proportion of Crenarchaeota at 51.2%, with the proportion of Euryarchaeota at 48.8%, whereas the permafrost contained 41.2% Crenarchaeota and 58.8% Euryarchaeota , based on 16S rRNA gene sequence analysis. OTU1 and OTU11, affiliated to Group 1.3b/MCG-A within Crenarchaeota and the unclassified group within Euryarchaeota , respectively, were widely distributed in all sediment layers. However, OTU5 affiliated to Group 1.3b/MCG-A was primarily distributed in the active layers. Sequence analysis of the DGGE bands from the 16S rRNAs of methanogenic archaea showed that the majority of methanogens belonged to Methanosarcinales and Methanomicrobiales affiliated to Euryarchaeota and the uncultured ZC-I cluster affiliated to Methanosarcinales distributed in all the depths along the permafrost profile, which indicated a dominant group of methanogens occurring in the cold ecosystems.